2013
DOI: 10.1007/s10815-013-0116-9
|View full text |Cite
|
Sign up to set email alerts
|

Resveratrol treatment during goat oocytes maturation enhances developmental competence of parthenogenetic and hand-made cloned blastocysts by modulating intracellular glutathione level and embryonic gene expression

Abstract: Purpose The aim of the present study was to determine whether supplementation of resveratrol, a stilbenoid antioxidant with therapeutic significance, influences goat (Capra hircus) oocyte maturation and subsequent embryonic development and expression of apoptosis and early embryonic development-related genes. Methods Five different concentrations of resveratrol (0.1, 0.25, 0.5, 2.0 and 5.0 μM) were used in in vitro maturation (IVM) medium. Cell tracker blue and 2′,7′-dichlorodihydrofluorescein diacetate (H 2 D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
72
2
23

Year Published

2015
2015
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 95 publications
(120 citation statements)
references
References 46 publications
(54 reference statements)
13
72
2
23
Order By: Relevance
“…The increased level of GSH was coupled with reducing the intracellular levels of ROS, oxidative stress-induced apoptosis, and altering the expression of oocytes' molecular markers during IVM (Kwak et al, 2012;Kim et al, 2015;Jin et al, 2016). In support to this assumption, addition of resveratrol during IVM of goat COCs has significantly reduced both intracellular ROS and expression of proapoptotic (Bax) gene while increasing GSH levels (Mukherjee et al, 2014).…”
Section: Discussionmentioning
confidence: 83%
“…The increased level of GSH was coupled with reducing the intracellular levels of ROS, oxidative stress-induced apoptosis, and altering the expression of oocytes' molecular markers during IVM (Kwak et al, 2012;Kim et al, 2015;Jin et al, 2016). In support to this assumption, addition of resveratrol during IVM of goat COCs has significantly reduced both intracellular ROS and expression of proapoptotic (Bax) gene while increasing GSH levels (Mukherjee et al, 2014).…”
Section: Discussionmentioning
confidence: 83%
“…Therefore, it is necessary to identify the factors/conditions that improve Bcl2 but reduce Bax expression in the cultured follicles in future studies. Mukherjee et al [35] reported that resveratrol reduces the expression of Bax genes in goat oocytes. Similarly, estradiol suppressed apoptosis in the rabbit CL by altering the expression of Bcl2 family of genes [36].…”
Section: Discussionmentioning
confidence: 99%
“…These effects of resveratrol seem more likely to be associated with increasing telomere length and telomerase activity and reduction of germ cell dysfunction. Mukherjee et al (2014) showed that the supplementation of resveratrol at optimum concentrations during IVM improves the microenvironment within oocytes by increasing the intracellular GSH and decreasing the ROS level, thus stimulating embryonic development, and regulating gene expression (Mukherjee et al, 2014). Several studies have evaluated the effect of resveratrol as a novel treatment modality for polycystic ovary syndrome.…”
Section: The Immunohistochemical Analysis For Amh-positive Follicles mentioning
confidence: 99%